Effects of the EU food safety regulation on cadmium on the cacao value chains of Colombia, Ecuador, and Peru - Charry, Andres; Atkinson, Rachel; Junca Paredes, Jhon Jairo; Perea Ramirez, Carolay; Thomas, Evert; Pulleman, Mirjam Margreet (2023)
This briefing note combines information from three country reports conducted between 2021 and 2022, as well as relevant findings from the available literature to examine the current state of knowledge of the spatial distribution of Cd content in cacao farms in the three countries, how the EU regulation has affected different stakeholders, and how they are managing the problem. With the information presented in this document, we also improve and update literature available to date.